2000
DOI: 10.1007/s004280000200
|View full text |Cite
|
Sign up to set email alerts
|

Collagen alteration in vascular remodeling by hemodynamic factors

Abstract: The collagen alterations in the vascular wall remodeled by hemodynamic change were investigated by electron microscopy and immunohistochemistry. The left anterior descending coronary artery (LAD) without a myocardial bridge (MB) showed both lower matrix metalloproteinase-1 (MMP-1) expression and a smaller extent of spiraled collagen (SC) distribution than the LAD wall with MB, in which the intima was influenced by high shear stress. In the wall of the varicose great saphenous vein (GSV) the expression of MMP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 31 publications
1
36
1
Order By: Relevance
“…Therefore, we investigated the regulation of cerebrovascular MMPs that can degrade collagen (MMP-1) and gelatin (MMP-2 and -9). Increased extracellular matrix protein synthesis, diminished MMP activity, and/or increased TIMP activity all could contribute to matrix accumulation, which is a late event in the vascular remodeling process (36). Interestingly, recent studies demonstrated that MMP activation also contributes to vascular smooth muscle cell growth and migration as well as increased collagen synthesis via several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated the regulation of cerebrovascular MMPs that can degrade collagen (MMP-1) and gelatin (MMP-2 and -9). Increased extracellular matrix protein synthesis, diminished MMP activity, and/or increased TIMP activity all could contribute to matrix accumulation, which is a late event in the vascular remodeling process (36). Interestingly, recent studies demonstrated that MMP activation also contributes to vascular smooth muscle cell growth and migration as well as increased collagen synthesis via several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…With increased flow, an upregulation of ECM genes, including collagen genes in the pulmonary artery [37], an increase of spiraled collagen in coronary arteries [38] and in collagen turnover [39] has been reported. In vitro, the gene expression of TGF尾1, a cytokine well-known to enhance collagen deposition, was increased in vascular smooth muscle cells exposed to shear stress [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other factors, such as hemodynamic [13] and molecular [21] factors, are expected to elucidate this issue. Shear stress, in particular, is considered to be an important factor, because it affects regional metabolism of cellular and matrix components, such as collagens, in the intima [11].…”
Section: Correlation Between the Distributions Of Dit And Those Of Atmentioning
confidence: 99%